Crime in the United States 2004 - (:unkn) unknown (My University, 2016)
Crime in the United States (CIUS) is an annual publication in which the FBI compiles volume and rate of crime offenses for the nation, the states, and individual agencies. This report also includes arrest, clearance, and law enforcement employee data.